2023
DOI: 10.1002/adfm.202303869
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel Sonocatalysis Amplifiers Target IDH1‐Mutated Tumor Plasticity and Attenuate Ros Tolerance to Repress Malignant Cholangiocarcinoma

Abstract: Tumor adaptation‐originated tumor tolerance that compensatory mechanisms (e.g., isocitrate dehydrogenase (IDH) mutation) jointly shape is the dominant obstacle of ROS therapy. Currently, targeting a single pathway fails to fundamentally reverse the complex milieu and diminish tumor adaptation. Herein, a multichannel sonocatalysis amplifier is engineered via one‐pot gas diffusion method to attenuate IDH1‐mutated cholangiocarcinoma plasticity and tolerance to ROS therapy, wherein triptolide and IR780 are co‐load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Moreover, FSC + US significantly reduced the GSH compared with other groups, revealing the efficient GSH depletion ability. The ratio of GSH/GSSG is considered a powerful index of oxidative stress ( Wang D. et al, 2023 ; Liu et al, 2023 ). The results showed that in the Fe 3 O 4 @SiO 2 and FSC treatment groups, the GSH/GSSG ratio was slightly varied, while it was greatly decreased in FSC + US group ( Figure 4D ), altogether confirming the superiority of FSC sonodynamic therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, FSC + US significantly reduced the GSH compared with other groups, revealing the efficient GSH depletion ability. The ratio of GSH/GSSG is considered a powerful index of oxidative stress ( Wang D. et al, 2023 ; Liu et al, 2023 ). The results showed that in the Fe 3 O 4 @SiO 2 and FSC treatment groups, the GSH/GSSG ratio was slightly varied, while it was greatly decreased in FSC + US group ( Figure 4D ), altogether confirming the superiority of FSC sonodynamic therapy.…”
Section: Resultsmentioning
confidence: 99%
“…With advancements in scientific and technological progress, chemodynamical therapy (CDT) has emerged as a viable alternative for tumor treatment in recent years [17]. CDT operates by converting intracellular H 2 O 2 into •OH using the iron Fenton reaction, leading to lethal toxicity specifically targeting tumor cells [18,19]. Consequently, the current research primarily concentrates on the development of nanocarriers and nano catalysts capable of transporting Fenton catalysts or metal ions [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%